Chemical-sensory properties and consumer preference of hibiscus beverages produced by improved industrial processes. (15th June 2017) - Monteiro, Maria João P.; Costa, Ana Isabel A.; Fliedel, Geneviève; Cissé, Mady; Bechoff, Aurélie; Pallet, Dominique; Tomlins, Keith; Pintado, Maria Manuela E.
Highlights: Three hibiscus beverages produced by improved manufacturing processes in Senegal were studied. They had high colour density, anthocyanin and polyphenolic content and antioxidant capacity. Their main attributes were a deep red colour, strong aromatics and balanced sweetness and acidity. Relations between sensory/consumer evaluations and physicochemical results were uncovered. Consumers preferred the new beverages to a conventional one, regardless of demographics or habits. Abstract: The need to increase sustainability and add value to traditional foods claiming health benefits led to the introduction of key improvements in the production of hibiscus beverages in Senegal. The physicochemical and sensory properties of three resulting products (an under-vacuum concentrate, a dilute-to-taste syrup and a ready-to-drink infusion) were assessed, vis-à-vis those of conventionally manufactured beverages, and their impact on local consumer preference determined (n = 146). New beverages had more intense, redder colour and higher monomeric anthocyanin content, total phenolic content and antioxidant capacity. Moreover, their colour evaluations by trained panellists were mainly linked to colour density and anthocyanin/polyphenol content, while flavour assessments were associated to titratable acidity and sugar-to-acid ratio. Consumer evaluations, in turn, were driven by the beverages' red colour intensity, aroma strength and balance between sweetness and acidity. This explained why they overwhelmingly preferred the under-vacuum concentrate, regardless of their age, gender or frequency of hibiscus beverage consumption.